Persepsi Followers Terhadap Akun Instagram @infotije dalam Memenuhi Kebutuhan Informasi Pelanggan Transjakarta - Livana Aisya; Dian Alfia Purwandari; Nandi Kurniawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This study aims to analyze the perceptions of Transjakarta users towards the Instagram account @infotije in terms of meeting their information needs. The type of research used is descriptive research with a qualitative approach. Data collection techniques in this study include observation, interviews, and documentation. The results of the study show that the Instagram account @infotije is effective in enhancing users' knowledge about Transjakarta services, which include routes, schedules, service changes, and special facilities. This study also evaluates the approach to users' information needs, which are current, daily, in-depth, and concise. It was found that the @infotije account successfully meets the need for up-to-date and relevant information, although there is room for improvement in interaction and response to user questions. Overall, the Instagram account @infotije plays an important role in the information ecosystem of Transjakarta users, helping them plan their journeys more efficiently and increasing their trust in Transjakarta services.